Flowchart-based Bayesian Intelligent Tutoring System for computer programming - Hooshyar D.; Ahmad R.B.; Fathi M.; Yousefi M.; Hooshyar M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Bayesian networks; Computer aided instruction; Computer programming; Decision making; Education computing; Flowcharting; Problem solving; Smart sensors; Flowchart development; Intelligent tutoring system; Knowledge level; Learning programming; Novice programmer; Prior knowledge; Problem solving skills; Target audience; Computer systems programming